Family Socioeconomic Status at Birth and Youth Impulsivity at Age 15; Blacks' Diminished Return - Shervin Assari; Cleopatra Howard Caldwell; Ron Mincy (MDPI AG, 2018)
Minorities’ Diminished Return theory suggests that health effects of socioeconomic status (SES) are systemically smaller for racial and ethnic minorities compared to Whites. To test the relevance of Minorities’ Diminished Return theory for youth impulsivity, we investigated Black–White differences in the effects of family SES at birth on subsequent youth impulsivity at age 15. Data came from the Fragile Families and Child Wellbeing Study (FFCWS), 1998–2016, a 15-year longitudinal study of urban families from the birth of their children to age 15. This analysis included 1931 families who were either White (n = 495) or Black (n = 1436). The independent variables of this study were family income, maternal education, and family structure at birth. Youth impulsivity at age 15 was the dependent variable. Gender was the covariate and race was the focal moderator. We ran linear regressions in the overall sample and specific to each race. In the overall sample, higher household income (b = −0.01, 95% CI = −0.01 to 0.00) and maternal education (b = −0.24, 95% CI = −0.44 to −0.04) at birth were associated with lower youth impulsivity at age 15, independent of race, gender, and family structure. A significant interaction was found between race and household income at birth (b = 0.01, 95% CI = 0.00 to 0.02) on subsequent youth impulsivity, which was indicative of a stronger protective effect for Whites compared to Blacks. Blacks’ diminished return exists for the long-term protective effects of family income at birth against subsequent youth impulsivity. The relative disadvantage of Blacks in comparison to Whites is in line with a growing literature showing that Black families gain less from high SES, which is possibly due to the existing structural racism in the US.